1473 In patients with chest pain suspicious for ACS, is arrival by emergency ambulance associated with increased likelihood of myocardial infarction?. Issue 12 (22nd November 2022) - Murray, James; Raja, Edwin Amalraj; Cooper, Jamie
Abstract : Aims, Objectives and Background: Patients commonly present to the Emergency Department (ED) with chest pain suspicious of an acute coronary syndrome (ACS). Clinical features and historical risk factors for ACS are assimilated with electrocardiographic (ECG) findings and cardiac biomarkers to assess risk, determine diagnosis and decide subsequent disposition. Many such patients arrive by ambulance but whether the mode of arrival is associated with an increased likelihood of myocardial infarction is unknown. Method and Design: Adult patients (≥16 years) presenting to Aberdeen Royal Infirmary ED with chest pain suspicious of ACS and non-diagnostic ECGs were identified from two prospectively collected cohorts. Patient demographics, known ACS risk factors at presentation, cardiac biomarker results and clinical outcomes up to 30 days were recorded. Data sets were retrospectively interrogated electronically to identify the mode of ED arrival: by ambulance, or other. The independently adjudicated primary outcome was the development of type 1 or 4 myocardial infarction or cardiac death at 30 days. Logistic regression was used to determine the association between mode of arrival and the primary outcome after adjusting for other confounds. The strength of association was reported as odds ratio (OR) and adjusted odds ratio (aOR) and its 95% confidence interval (CI). Statistical analysis was performed using SPSS v27. A p-value <0.05 was considered to be statistically significant. Results and Conclusion: Of 1606 patients [mean age 62 (SD 16) years, 45% women], 1246 (78%) arrived via ambulance and 188 (12%) reached the primary outcome. After adjusting for known confounders, a statistically significant association (aOR 1.72; 95% CI 1.11 to 2.66) between ED arrival by ambulance and the development of type 1 or type 4 myocardial infarction or cardiac death at 30 days was demonstrated ( table 1 ). In our cohort of patients with chest pain suspicious of ACS, ED arrival by ambulance correlates strongly with the development of myocardial infarction at 30 days.